Location estimation techniques (determination and prediction) techniques in smart environments - MISRA, Archan (Institutional Knowledge at Singapore Management University, 2005)
A smart environment is, by definition, context‐aware : by combining inputs from multiple pervasive sensing devices, applications in the smart infrastructure should be able to intelligently deduce the intent or attributes of an individual without explicit manual input. Location is perhaps one of the earliest, and still most common, examples of such context. There are myriad examples of pervasive applications where the system uses the location of a mobile individual, or sometimes groups of individuals, to customize or adapt to the computing environment. A smart environment must be able to both determine and predict the location of an individual. In this chapter, we shall look at the various protocols, algorithms and technologies used for effective location prediction in smart environments. We shall first study the various research prototypes and techniques used to obtain the location information of a mobile user or device in a smart environment. We will then develop a unifying approach toward location prediction and finally concentrate on the problem of location prediction for both the geometric and symbolic group of location reporting technologies.